Influence of Celery Leaf Substitution on the Sodium and Potassium Composition of a Functional Cucumber Powder Drink for Hypertension Management - Ramadhani, Nurul Putri; Junita, Dini (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2025)
Functional beverages innovatively formulated from natural ingredients such as cucumber (Cucumis sativus L.) and celery (Apium graveolens L.) contain abundant bioactive compounds with antihypertensive properties, offering a nutritious and safe alternative to support the prevention and management of hypertension. This study aimed to determine the effect of celery extract powder substitution on the organoleptic properties and the sodium and potassium contents of functional cucumber powder drinks. This experimental research employed a non-factorial Completely Randomized Design (CRD) consisting of three treatments and three replications. The parameters tested included acceptability (color, taste, aroma, and texture) through hedonic testing by semi-trained panelists, as well as sodium and potassium analysis conducted at the Center for Standardization and Industrial Services. Data were analyzed using ANOVA, followed by Duncan’s test when significant differences were observed. The highest mean scores for color and aroma were obtained in treatment P (50% celery: 50% cucumber), for taste in treatment R (60% celery: 40% cucumber), and for texture in treatment N (40% celery: 60% cucumber), with all treatments categorized as “slightly liked.” Treatment N (40% celery: 60% cucumber) showed the lowest sodium content (3.85 mg/200 ml, 0.25% RDA) and the highest potassium content (24.21 mg/200 ml, 0.51% RDA). Substitution of celery leaf powder in treatments N, P, and R had no significant effect on color, taste, aroma, or texture, but significantly affected sodium and potassium levels. The formulation in treatment N (40% celery: 60% cucumber) demonstrated the greatest potential as a functional beverage for hypertension management.